2016
DOI: 10.1002/art.39786
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase–Antineutrophil Cytoplasmic Antibody (ANCA)–Positive Granulomatosis With Polyangiitis (Wegener's) Is a Clinically Distinct Subset of ANCA‐Associated Vasculitis: A Retrospective Analysis of 315 Patients From a German Vasculitis Referral Center

Abstract: Patients with MPO-ANCA-positive GPA show significantly different clinical courses compared to those with PR3-ANCA-positive GPA or MPO-ANCA-positive MPA, which should be considered in their clinical management. Classification according to ANCA specificity may improve the evaluation of relapse risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
80
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 45 publications
10
80
1
5
Order By: Relevance
“…Recently, GPA patients with MPO-ANCA were reported to have different clinical features from those with PR3-ANCA or those without. 30 To identify the influence of ANCA types on the disease course of GPA, we divided 30 patients into MPO-ANCA (eight patients), PR3-ANCA (17 patients) and ANCA negative (five patients) groups according to ANCA types, and we compared variables between the two groups as described in Table S2. We found that gender and alveolar hemorrhage showed significant differences between patients with MPO-ANCA and PR3-ANCA.…”
mentioning
confidence: 99%
“…Recently, GPA patients with MPO-ANCA were reported to have different clinical features from those with PR3-ANCA or those without. 30 To identify the influence of ANCA types on the disease course of GPA, we divided 30 patients into MPO-ANCA (eight patients), PR3-ANCA (17 patients) and ANCA negative (five patients) groups according to ANCA types, and we compared variables between the two groups as described in Table S2. We found that gender and alveolar hemorrhage showed significant differences between patients with MPO-ANCA and PR3-ANCA.…”
mentioning
confidence: 99%
“…Patients with MPO-ANCApositive GPA are predominantly females. They had limited disease, high incidence of subglottic stenosis, less need for immunosuppressive therapy, and lower relapse rates in comparison to patients with PR3-ANCA [63].…”
Section: Clinical Presentationmentioning
confidence: 98%
“…With the introduction of glucocorticoids and cyclophosphamide, the clinical course has become a chronic relapsing and remitting disease with remission noted in 90% of the patients. Increased risk for relapse is associated with PR3-ANCA positivity and lung or ENT involvement [63]. The ANCA titer often rises in active disease.…”
Section: Prognosis or Clinical Coursementioning
confidence: 99%
“…Spinal cord involvement represents a rare complication of granulomatosis with polyangiitis (GPA). [1][2][3] Hypertrophic pachymeningitis, as a possible manifestation, can arise in proteinase-3 antibody (anti-PR3) positive cases as well as in myeloperoxidase antibody (anti-MPO) associated GPA, whereas primary spinal angiitis seems to be a unique complication of anti-PR3 positive GPA. 4,5 Here, we report a case of long-term immunosuppressive treatment in a patient with anti-PR3 positive GPA, who developed an acute paraplegia caused by extensive pachymeningitis which despite treatment escalation only partially responded.…”
Section: Dear Editormentioning
confidence: 99%